2020
DOI: 10.21203/rs.3.rs-60955/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Isometric Strength Database for Muscle Maximal Voluntary Endurance Field Tests: Normative Data.

Abstract: Background: Different field tests are used to evaluate muscular capacity, in particular maximal voluntary endurance. However, although there are some normative values for a few muscle endurance tests, these do not consider the mass, size or age of individuals, which are well-known factors that influence muscle performance.Hypothesis/Purpose: The purpose of this study was to investigate the test-retest reliability of 8 field tests and establish muscle endurance norms, in an healthy population, based on their an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Therefore, we suggest that clinicians consider taking the Isometric Endurance when determining function required for occupations for this clinical population. Janik et al (2020) provided the normative data that clinicians could refer to. Several studies have found that grip strength is related to hand dominance, hand span, width and length, the circumference of the forearm and middle finger length (Abaraogu et al, 2017;Anakwe et al, 2007;Kunelius et al, 2007;MacDermid et al, 2002;Shurrab et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we suggest that clinicians consider taking the Isometric Endurance when determining function required for occupations for this clinical population. Janik et al (2020) provided the normative data that clinicians could refer to. Several studies have found that grip strength is related to hand dominance, hand span, width and length, the circumference of the forearm and middle finger length (Abaraogu et al, 2017;Anakwe et al, 2007;Kunelius et al, 2007;MacDermid et al, 2002;Shurrab et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we suggest that clinicians consider taking the Isometric Endurance when determining function required for occupations for this clinical population. Janik et al (2020) provided the normative data that clinicians could refer to.…”
Section: Discussionmentioning
confidence: 99%